2006
DOI: 10.1207/s15327752jpa8702_08
|View full text |Cite
|
Sign up to set email alerts
|

The Deconstruction of the Hy Scale of MMPI–2: Failure of RC3 in Measuring Somatic Symptom Expression

Abstract: The MMPI-2 (Butcher, Dahlstrom, Graham, Tellegen, & Kaemmer, 1989) Clinical Scales have a long history in psychological assessment. Recently, Tellegen et al. (2003) conducted a series of analyses to restructure the scales to reduce what they considered to be problems that limit scale functioning. In a critique of the Restructured Clinical (RC) Scales published in this issue, Nichols (2006/this issue) questions a number of aspects of the approach Tellegen et al. took including their theoretical assumptions, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Although the correlation between RC9 and Scale 9 are reported to be .77 and .80 for men in two of the three clinical samples in the RC 435 Downloaded by [UNIVERSITY OF ADELAIDE LIBRARIES] at 21:45 17 November 2014 monograph, the community mental health sample of 410 men yielded a correlation of .26 for RC9 and Scale 9 (Tellegen et al, 2003). The low absolute value of the correlations between RC3 and Scale 3 for men (ranging from -.13 to -.20) and women (ranging from -.09 to .01) reported by the scale developers (Tellegen et al, 2003) and found by others (Butcher, Hamilton, Rouse, & Cumella, 2006) suggests there was no preservation of a "core" of Scale 3. Therefore, additional validation data are needed to identify the constructs measured by each of these scales.…”
mentioning
confidence: 86%
“…Although the correlation between RC9 and Scale 9 are reported to be .77 and .80 for men in two of the three clinical samples in the RC 435 Downloaded by [UNIVERSITY OF ADELAIDE LIBRARIES] at 21:45 17 November 2014 monograph, the community mental health sample of 410 men yielded a correlation of .26 for RC9 and Scale 9 (Tellegen et al, 2003). The low absolute value of the correlations between RC3 and Scale 3 for men (ranging from -.13 to -.20) and women (ranging from -.09 to .01) reported by the scale developers (Tellegen et al, 2003) and found by others (Butcher, Hamilton, Rouse, & Cumella, 2006) suggests there was no preservation of a "core" of Scale 3. Therefore, additional validation data are needed to identify the constructs measured by each of these scales.…”
mentioning
confidence: 86%
“…If the conversion V is to resurface in the RC scales profile, it would be expected that RC1 (akin to the Hs scale) would be elevated, RC2 (akin to the D scale) would be moderately elevated, and RC3 (akin to the inverse of the Hy scale) would be depressed. However, Butcher, Hamilton, Rouse, and Cumella (2006) argue that the restructuring of the Hy scale into RC3 resulted in a completely different scale. In particular, Butcher et al point out that the decision to compose RC3 entirely of a cynicism factor and not of a defensive somatization factor-in order to reduce overlap with RC1-has led the scale to drift too far away from McKinley and Hathaway's (1944) original intention.…”
Section: Mmpi-2 Restructured Formmentioning
confidence: 99%
“…Others, however, have pointed to flaws in this approach and the resulting RC Scales (e.g. Butcher, Hamilton, Rouse, & Cumella, 2006; Caldwell, 2006; Gordon, 2006; Nichols, 2006; Ranson et al., in press; Rogers & Sewell, 2006; Rogers, Sewell, Harrison, & Jordan, 2006). For example, Rogers and Sewell (2006, pp.…”
mentioning
confidence: 99%
“…Methodological Issues and Findings. Despite their name, which implies a close link to the MMPI‐2 Clinical Scales, the Restructured Clinical Scales are not simply shortened or alternative forms of the Clinical Scales (Butcher, Hamilton, et al., 2006; Nichols, 2006; Rouse, Greene, Butcher, Nichols, & Williams, 2008; Simms, Casillas, Clark, Watson, & Doebbeling, 2005), even though the RC Scales replace the Clinical Scales in the new MMPI‐2‐RF (Ben‐Porath & Tellegen, 2008). As Simms and colleagues (2005, p. 357) explained:…”
mentioning
confidence: 99%
See 1 more Smart Citation